Tissue characterization of the medical fungus Hericium coralloides by focus-variation microscopy. (4th July 2021) - Pallua, J. D.; Unterberger, S. H.; Pallua, A. F.; Pfaller, K.; Pallua, A. K.; Putzer, D.; Pöder, R.; Kirchmair, M.
ABSTRACT: In this study, the potential of focus-variation microscopic imaging was evaluated in a study of morphological patterns of the potential medicinal fungus Hericium coralloides (Basidiomycota). We created three-dimensional reconstructions and visualizations using the imaging technique on a fresh H. coralloides basidioma. The aim was to approximate the spore dispersal efficiency of this basidiomata type regarding the investment of tissue biomass and its reproductive output (production of basidiospores). Results were correlated with published data gained from magnetic resonance imaging and micro-computed tomography. It is demonstrated that focus-variation microscopic imaging results in a more distinct picture of the morphology of the edible and potentially medicinal H. coralloides basidiomata. However, a direct measurement of spore production was not possible. Spore production could only be estimated in combination with a mathematical model because the surface was not directly measurable due to the cellular heterogeneity. However, focus-variation microscopic imaging allows a better and faster estimation of spore production compared with the published methods. Furthermore, it was found that a scanning resolution of 5× is sufficient for determining the fungal surface precisely because at a higher resolution artifacts occur, resulting in adulteration of the image.